Comparison of extraction techniques for quantitative determination of rutin from morus alba linn. By reverse phase high performance liquid chromatography. - SHREEDA S. ADHYAPAK,; DR. VIDYA V. DIGHE,; VIJAY N. GOKARN,; NEETA S. SHAMBHU,; DHANASHRI Y. MESTRY, (International Journal of Pharma and Bio Sciences, 2011)
A simple, more efficient, less time consuming extraction technique has been developed for extraction of rutin, a flavonoid, from dry leaf powder of Morus alba Linn. Rutin was extracted from dried leaf powder of Morus alba Linn., using aqueous methanol as extracting solvent, using shaking extraction technique and ultrasonic extraction technique. The aqueous methanolic extracts obtained from these two techniques, were analysed by reverse phase HPLC method for quantitation of rutin. Chromatographic analysis was carried out on Cosmosil C18 column (150mm X 4.6mm, 5µm). The mobile phase used was a mixture of distilled water, methanol and triethylamine, in the volume ratio of 60:40:0.1, adjusted to pH 3.10, with orthophosphoric acid, at a flow rate of 1.0 mL/min. The UV detection was carried out at 256 nm.